2016
DOI: 10.1093/molehr/gaw066
|View full text |Cite
|
Sign up to set email alerts
|

Uterosome-like vesicles prompt human sperm fertilizing capability

Abstract: The project was financially supported by SECyT-UNC. The authors declare no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…interactions between EVs of uterine or oviductal origin and spermatozoa may occur in a short time interval: even a 15-min incubation of spermatozoa with fluorescent labeled uterine EVs was sufficient to retrieve sperm with fluorescent staining, indicating the rapid fusion of EVs with sperm membrane (Franchi et al 2016). Thus, it may be that some of the sperm-interacting proteins identified in the present study were delivered to sperm membrane after fusion with oviductal EVs.…”
Section: Figurementioning
confidence: 66%
“…interactions between EVs of uterine or oviductal origin and spermatozoa may occur in a short time interval: even a 15-min incubation of spermatozoa with fluorescent labeled uterine EVs was sufficient to retrieve sperm with fluorescent staining, indicating the rapid fusion of EVs with sperm membrane (Franchi et al 2016). Thus, it may be that some of the sperm-interacting proteins identified in the present study were delivered to sperm membrane after fusion with oviductal EVs.…”
Section: Figurementioning
confidence: 66%
“…As we previously observed that uterosome‐like vesicles increase the human sperm iAR and PY, we evaluated the effect of oviductal EV on these capacitation parameters. The interaction of spermatozoa with EV from the isthmus or ampulla region increases 2.5‐fold the iAR, as similarly observed by uterosome‐like vesicles in human spermatozoa, and by vaginosomes after a brief interaction with murine spermatozoa prompted by progesterone …”
Section: Discussionmentioning
confidence: 99%
“…After seminal plasma removal, sperm suspensions were incubated for 90 minutes under different conditions: Non‐Cap, “non‐capacitating” medium (Sp‐TALP formulated as described above); Non‐Cap medium containing 10 µg/mL of EV (from isthmus or ampulla) or “capacitating” medium as control of capacitating conditions (Sp‐TALP supplemented with 25 mM NaHCO 3 and 3 mg/mL BSA; Sigma; Cat #A‐7906). The EV concentration was selected based on data from previous results and referred to the protein concentration.…”
Section: Methodsmentioning
confidence: 99%
“…After leaving the vagina sperm enter the uterus. In vitro studies have shown that a short exposure (15 min) of sperm with uterosomes secreted by endometrial epithelial cells simulating the time that they spend in the uterus is enough to enhance sperm capacitation status in human spermatozoa [26]. Others authors have described the same results but with longer exposure times [21].…”
Section: Relationship Between Spermatozoa and Evs As A Tool To Enhancmentioning
confidence: 96%